2011
DOI: 10.1002/pola.25049
|View full text |Cite
|
Sign up to set email alerts
|

Exhaustive and partial alkoxylation of polymethylhydrosiloxane by copper‐catalyzed dehydrocoupling with alcohols: Synthesis, crosslinking behavior, and thermal properties of the products

Abstract: Polymethylhydrosiloxane (PMHS) reacts with aliphatic and aromatic alcohols at room temperature in the presence of [CuH(PPh 3 )] 6 complex catalyst to give poly[(methyl) (alkoxy)siloxane]s in high yields. Reactivity of alcohols decreases in the order of p-methoxyphenol > p-cresol > phenol > benzyl alcohol > allyl alcohol > ethanol > isopropanol > tert-butyl alcohol. Partially p-cresylated polymers, which still retain unreacted SiAH bonds, react further with ethylene glycol or water to form cross-linked polymers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…2 To the best of our knowledge, the current types of functionalization of polysiloxane Si-H bonds are limited to the formation of new Si-O-R (R=alkyl, aryl, acyl) and Si-R (R=alkyl) bonds (Scheme 1) in polysiloxane oils. For example, Cu 7 and Zn 8 based catalysts, and tris(pentafluorophenyl)borane (B(C 6 F 5 ) 3 ) 9 are known to catalyze the synthesis of functionalized PMHS (polymethylhydrosiloxane) via dehydrogenative coupling using alcohols or carboxylic acids (Scheme 1a). However, when the formation of new Si-C bond is preferred, there is only one example in the literature where a non-precious metal Ni complex was successfully used to functionalize PMHS with 1hexene or 1-octene (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%
“…2 To the best of our knowledge, the current types of functionalization of polysiloxane Si-H bonds are limited to the formation of new Si-O-R (R=alkyl, aryl, acyl) and Si-R (R=alkyl) bonds (Scheme 1) in polysiloxane oils. For example, Cu 7 and Zn 8 based catalysts, and tris(pentafluorophenyl)borane (B(C 6 F 5 ) 3 ) 9 are known to catalyze the synthesis of functionalized PMHS (polymethylhydrosiloxane) via dehydrogenative coupling using alcohols or carboxylic acids (Scheme 1a). However, when the formation of new Si-C bond is preferred, there is only one example in the literature where a non-precious metal Ni complex was successfully used to functionalize PMHS with 1hexene or 1-octene (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%
“…by the elimination of hydrogen molecules. To this date, most of researchers are mainly focused on the dehydrocoupling between alcohol and hydrosilane (or hydrosiloxane), 39,40 and the reaction between other active hydrogen (like NH 2 , HS and C]N-OH) and Si-H is seldom investigated. Hence, we prepare a novel crosslinker PMKS by dehydrogenation between acetoxime and PMHS to vulcanize silicone rubber at 25 C.…”
Section: Synthesis and Characterization Of Pmks And Novel Rtv Siliconmentioning
confidence: 99%
“…29,30 These experiments have been mostly conducted in dry toluene, 19,21,22 or benzene. 29,31 On the alcoholysis of PMHS, Safa et al implemented the Speier's and Karstedt's catalysts in xylene, which were found to be applicable for primary and secondary alcohols. 18 The most recent study, by Jur askov a et al monitored the ethanolysis of PMHS (7%-9%, 15%-18%, and 45-55% H-functionalized) among other hydrosiloxanes which are widely known in the silicone industry.…”
Section: Introductionmentioning
confidence: 99%
“…Namely, potassium hydroxide, 21–25 hexachloroplatinic acid, 23,25,26 Speier's or Karstedt's catalyst, 18,19 Pt/C, 21 palladium nanoparticles and rhodium complex, 27,28 also copper and tetrabutylammonium fluoride catalysts have been considered 29,30 . These experiments have been mostly conducted in dry toluene, 19,21,22 or benzene 29,31 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation